Maugham's Philosophical Views and Their Role in Shaping His Aesthetics - Bahodirovna, Tagaeva Tamara (Researchparks Publishing, 2023)
This article explores the philosophical views of S. Maugham, which influenced the condescension and understanding of the author's personality. William Somerset Maugham is primarily known as a playwright, short story writer, and novelist; he is not a creator of literary theory in the strict sense of the word, but his numerous observations on his own work and that of other writers; his literary criticism of certain Russian and Western classics; his philosophical and aesthetic sketches allow us to speak of him as a major and extraordinary scholar of literature, who offered his original conception of the novel.